Prevalence and antimicrobial resistance of Salmonella and pathogenic E. coli in broiler farms, Wakiso district, Uganda - Thomas Ssemakadde; Nalumaga Pauline Petra; Jude Collins Busingye; Joel Bazira; Kabanda Taseera (PLoS ONE, 2025)
Background The emergence and re-emergence of zoonotic bacterial infections and the upsurge reflected in current trends of antimicrobial-resistant bacteria is a major global concern. Salmonella spp and Escherichia coli (E. coli) are the two most important food-borne pathogens of public health interest incriminated in poultry products worldwide. AMR in poultry farming poses a significant public health risk in Uganda, as the misuse and overuse of antibiotics in livestock can lead to the emergence of resistant pathogens that may transfer to humans through direct contact, consumption of contaminated poultry products, or environmental exposure, further complicating the management of infection hence necessitating constant monitoring of microbial food safety measures. Methods This study was a cross-sectional study that used a total of two hundred sixteen poultry samples from cloacae swabs and fecal swabs collected from broiler poultry farms. These were cultured on Chromagar TM Salmonella and Sorbitol MacConkey agar. Biochemical tests, minimum inhibitory concentration, and polymerase chain reaction were utilized. Data was analyzed by descriptive statistics, and Chi-square (χ²) Test statistical significance of quantitative data. Results A total of 40 (18.5%) Salmonella and 120 (55.6%) pathogenic E. coli were isolated while extended beta-lactamase (ESBL) production was detected in 18 Salmonella and 57 pathogenic E. coli isolates. Prevalence of blaTEM gene was expressed in 7/18 (39%) Salmonella isolates and 42/57 (73.8%) Pathogenic E. coli isolates The significant associated factors that predisposed these farms to Salmonella spp was source of poultry feeds (p-value = 0.066) while factors associated with pathogenic E. coli included contact of poultry with other birds and livestock (p-value = 0.020), movement from one pen to the other by farm-handlers (p-value = 0.017), use of untreated water (p-value = 0.018) and food contamination of commercial poultry feeds (p-value = 0.0021). Conclusion The findings of this study highlight the significant presence of Salmonella and pathogenic E. coli in poultry farms, underscoring the potential risks to public health. The high prevalence of antimicrobial resistance observed among these isolates calls for urgent interventions to curb the misuse of antibiotics in poultry farming.